Proses Pembelajaran Pendidikan Jasmani Adaptif Anak Tuna Rungu di SLB Negeri Se Kabupaten Simalungun - Lubis, Riska Syafrina Aulia; Valianto, Budi; Tantri, Afri (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research aims to determine the physical education learning process for deaf children in State Special Schools in Simalungun Regency as seen from the objectives, materials, student attitudes and motivation, teacher competence, facilities and infrastructure, and evaluation. This research is a descriptive research. The method used is a survey with data collection techniques using questionnaires. The research population was all state special school adaptive physical education teachers in Simalungun, totaling 13 teachers. This research is population research. The variable in this research is the physical education learning process for deaf children. The instrument used was a questionnaire. Validity test uses total item correlation and reliability uses Cronbach's alpha. The data analysis technique uses descriptive percentages. The results of the research show that the physical education learning process for deaf children in State Special Schools in Simalungun Regency is in the "poor" category 3 teachers (23.08%), in the "medium" category 7 teachers (53.85%), in the "good" category 1 teacher (7.69%), category "very good" 2 teachers (15.38%). Thus, it can be concluded that the physical education learning process for deaf children in state special schools throughout Simalungun Regency is in the medium category. Keywords: Adaptive Physical, Hearing Impaired, Learning